Unraveling ecological risk of As/Sb and other metal(loid)s and fungal community responses in As/Sb smelting-intensive zone: A typical case study of Southwest China. (1st March 2022) - Liu, Bang; Yao, Jun; Chen, Zhihui; Ma, Bo; Liu, Jianli; Li, Hao; Zhu, Xiaozhe; Li, Miaomiao; Cao, Ying; Pang, Wancheng; Zhao, Chenchen; Mihucz, Victor G.; et al.
Abstract: Compound metal(loid)s are always occurred adjacent smelting-intensive zone. However, little is known with respect to the relative influences of As/Sb and other metal(loid)s on human health and fungal communities as a consequence of the chronic As/Sb smelting fabrication. Our objectives were to determine the ecological impacts of the occurrences of As/Sb and other metal(loid)s on human health and fungal communities via diverse indices and Internal Transcribed Spacer (ITS) sequencing in this study. Three vegetated soils exhibited exceptional metal(loid)s enrichment of As, Sb, Cr, Ni, Zn, Mn, Cu and Pb. Higher health risks of As, Sb and Pb were observed in all soils, accounted for over 80% of total health risk. ITS sequencing revealed that fungal communities among three vegetated soils were significantly different in their structures and compositions, and the metal(loid)s types and contents contributed differently to the variations. Fungal community in forest soil was mainly influenced by metal(loid)s, while in maize and rice soil were associated with pH, TC, TOC, TN and TP. Fungal communities were dominated by Ascomycota, followed by Mortierellomycota and Basidiomycota. Linear Discriminate Analysis Effect Size (LefSe) analysis revealed that tolerant taxa affiliated with distinct phylogenetic lineages were vegetation-specific. 25 potential keystone fungal taxa were identified mainly belonged to Dothideomycetes, Orbiliomycetes and Saccharomycetes . Our results may serve as a model for similar metal(loid)s contaminated areas and provide theoretical guidances for bioremediation of metal(loid)s pollution. Graphical abstract: Image 1 Highlights: Potential ecological risks of metal(loid)s and effects on indigenous fungi. As, Pb and Sb posed major health risk to mankind especially children. Differences in fungal structures and compositions around smelting zone. 25 keystone taxa affiliated with different phylogenetic lineages were identified.